Is stroke early supported discharge still effective in practice? A prospective comparative study - Fisher, Rebecca J.; Cobley, Christine; Potgieter, Iskra; Moody, Amy; Nouri, Fiona; Gaynor, Catherine; Byrne, Adrian; Walker, Marion F. (SAGE, 2016)
Objective: Randomised controlled trials have shown the benefits of Early Supported Discharge (ESD) of stroke survivors. Our aim was to evaluate whether ESD is still beneficial when operating in the complex context of frontline healthcare provision.